Slovenski sistem socialnega varstva otrok in družin s podsistemom zaščite otrok - Šeme, Mojca (Socialno delo, 2025)
Conceptualization of the Slovenian child and family social welfare system with the child-protection subsystem is presented and situated within selected international typologies. Using descriptive and interpretative meth- ods, together with a discourse-sensitive review of sources, the historical, political, and legislative influences that have shaped the current orientation of the system are analysed. The findings indicate that, following Slo- venia’s independence, a combined system initially emerged, integrating elements of conservative-corporatist systems and social-democratic systems – both types of systems being primarily oriented toward the provision of family support services. Over the past decade and more, however, the global economic crisis, the reorgan- ization of social work centres, legislative changes, austerity pressures, and other factors have contributed to the strengthening of elements within the system that are characteristic of neoliberal child protection systems, which are typically primarily focused on child protection rather than on the provision of family support services. At the same time, a child-centred pattern has also been strengthening within the Slovenian system over the past decade, in line with international trends. Within the Slovenian system, it is necessary to strengthen those elements that are primarily oriented toward the provision of family support services, as this enables the state to fulfil the constitutional principle of the social welfare state.
Keywords: centri za socialno delo; družinska politika; early help; family policy; family support; neoliberalism; neoliberalizem; podpora družinam; social work centres; zgodnja pomoč